Complex stab related injuries involving the diaphragm, bowel and cystic duct: a case report - Jain, Yash; Quraishi, Abdul Haque M.; Tongse, Pankaj (International Surgery Journal, 2024)
Penetrating abdominal trauma is a major killer worldwide. Biliary duct injuries resulting from penetrating stab wounds are rare but potentially life-threatening occurrences. This case report outlines a rare case, diagnosis, surgical management, and postoperative outcomes of a patient who sustained a cystic duct injury due to a penetrating stab wound. There is paucity of such cases in the literature. A 55-year-old man sustained a penetrating wound and was found to have cystic duct injury intra-operatively along with other multi-visceral injury. The patient underwent a cholecystectomy with the management of associated injuries. The report aims to highlight the rarity yet the possibility of such injuries and emphasize the importance of a high index of suspicion.